Multicriteria assessment of recently implemented conservation agriculture cropping systems across farmers’ plots in northwestern Cambodia - Sambo Pheap; Alexis Thoumazeau; Jun Murase; Vang Seng; Jean-Pierre Sarthou; Veng Sar; Linda Kimbo; Soklin Kheam; Pheakdey Chan; Pao Srean; Samrith Leang; Lyda Hok; et al. (Farming System)
Soil fertility depletion is a major challenge for annual rainfed cropping systems in the northwestern region of Cambodia which has recently undergone rapid agrarian changes. On-farm impacts of conventional tillage and Conservation Agriculture-based practices (CT and CA respectively) of maize cultivation on soil health along with agronomic and economic performances were compared. The experiment was set up in 2020 comparing CT and CA with one cover crop (CAS) and CA with a mix of three cover crops (CAM). Soil health was assessed at the end of the cropping cycle using Biofunctool®. Agronomic performances including cover crops and a cash crop (maize) along with intermediate consumption were recorded in 2021 and 2022. Selected components of soil health, agronomic and economic performances were used for multi-criteria analysis. On this Mollisols, SHI was positively impacted under CA (15% and 6% higher in 2021 and 2022), but with some soil parameters varied from one year to the next. In 2021, lower plant density (p ​< ​0.05) was recorded under CA, highlighting the need to improve the efficiency of no-till sowing methods. Intermediate consumption was not significant between the treatments for both years. Non-significant difference in yields was recorded under the three treatments in both years, but while both CA systems remained stable, CT dropped by 10% in 2022 with some differences for yield components with a larger number of grains per column and higher mass of grains under CAS. Gross value added under CA was 12.7% less than CT in 2021, it surpassed CT by 43% in 2022. Agronomic and economic performances were still unstable at this early stage of implementation with wide variability across the two cropping seasons emphasizing that with this soil type, CA induced a significant increase in soil health but did not yet lead to significant increase in productivity or economic outcomes.